Surface characterisation of V(2)O(5)/TiO(2) catalytic system - Rodella, C. B.; Nascente, PAP; Franco, RWA; Magon, C. J.; Mastelaro, V. R.; Florentino, A. O. (Wiley-Blackwell, 2001)
Samples of the V(2)O(5)/TiO(2) system were prepared by the sol-gel method and calcined at different temperatures. Surface species of vanadium, their dispersion, as well as the structural evolution of the system were analysed by XRD, Raman, EPR, and XPS techniques. The results of XRD showed the evolution of TiO(2) from anatase phase to rutile. phase. The Raman spectra for calcination temperatures up to 500 degreesC showed a good dispersion of vanadium over titania in the form of monomeric vanadyl groups (V(4+)) and polymeric vanadates (V(5+)). At least three families of V4+ ions were identified by EPR investigations. Two kinds of isolated V(4+) species are placed in sites of octahedral symmetry, substituting Ti(4+) in the rutile phase. The third is formed by pairs of V(4+) species on the surface of titania. Above 500 degreesC part of superficial V(4+) is inserted into the,matrix of titania and part is oxidized to V(5+). The XPS results showed that the V/Ti ratio rises with increasing calcination temperature, indicating a smaller dispersion of vanadium.